Almanac for the Anthropocene : A Compendium of Solarpunk Futures - Wieland, Brontë Christopher; Wagner, Phoebe (Book collections on Project MUSE., 2022)
"Original voices from across the solarpunk movement, which positions ingenuity, generativity, and community as ways to resist hopelessness in response to the climate crisis.Almanac for the Anthropocene collects original voices from across the solarpunk movement, which positions ingenuity, generativity, and community as beacons of resistance to the hopelessness often inspired by the climate crisis. To point toward practical implementation of the movement's ideas, it gathers usable blueprints that bring together theory and practice. The result is a collection of interviews, recipes, exercises, DIY instructions, and more-all of it amounting to a call to create hope through action.Inspired by a commitment to the idea that there can be no environmental justice without decolonial and racial justice, Almanac for the Anthropocene unites in a single volume both academic and practical responses to environmental crisis"--